Virtual reality in production development projects - Söderback, Albin; Nguyen, Vuong (My University, 2023)
In industrial development, virtual reality (VR) is a tool with huge potential, especially as industries become increasingly digital. With the help of virtual reality, employees may perform otherwise dangerous manufacturing operations without getting hurt, or a designer might be able to discover problems with the production layout or model before it is assembled. Consequently, less expensive mistakes and rework occur, eventually saving the organizations money and lives. This bachelor's thesis explored the topic "Virtual Reality in Production Development Projects "and was conducted at Virtual Manufacturing AB. This project examines the benefits of VR technology in development projects and how currently existing hardware and software can be used to implement a Virtual reality workspace. By implementing a Virtual reality workspace, this project aims to enable the design team at Virtual Manufacturing to review their model's scale and ergonomics in a more immersive way. This is accomplished with the help of hardware (Meta Quest) and software (Unreal Engine) The findings presented in this thesis aim to empower both the organization and future engineers with the knowledge and insights needed to further harness the potential of VR in production projects.
Keywords: Virtual Reality, VR, Manufacturing, Development, Production, Visualisation, Oculus, Level of Detail (LOD)